Complete mitochondrial genome of Pelecanus crispus and its phylogeny. Issue 2 (3rd July 2019) - Huang, Tian; Wang, Yonghong; Zhou, Libo; Xu, Zhenggang
Abstract: The Dalmatian Pelican ( Pelecanus crispus ), in the order Pelecaniformes, its habitat is distributed in Europe, Asia, and Africa. It is a large waterfowl that is of international concern. In this study, we first sequenced and described the complete mitochondrial genome and phylogeny of P. crispus . The results showed that the whole genome of P. crispus was 16, 131 bp in length, and contained 13 protein-coding genes, 22 transfer RNA genes, two ribosome RNA genes, and one non-coding control region. The overall base composition of the mitochondrial DNA was 30.48% for A, 23.15% for T, 31.68% for C, and 14.69% for G, with a GC content of 46.37%. A phylogenetic tree of P. crispus in Pelecaniformes confirmed that P. crispus was sister to C. occidentalis . This information will be useful in the current understanding of the phylogeny and evolution of Pelecaniformes.